The Effects of Problem-Based Learning Model with Environmental Literacy-Oriented on the Elementary School Students' Narrative Writing Skills - Misbah Binasdevi; Idah Faridah Laily; Tamsik Udin; Syibli Maufur; Inayatul Ummah (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis research aimed to determine the effects of a problem-based learning model with environmental literacy-oriented on the elementary school students' narrative writing skills. Using the quasi-experimental method, this research employed a non-equivalent control group design. The research participants were 50 fifth-grade students of Islamic Elementary School (MI) Darul Qirom, consisting of 25 students in the experimental class and 25 students in the control class. The data were collected using a test instrument consisting of five questions about writing narratives. The data were then analyzed using the independent sampel t-test with the assistance of the SPSS application. The data analysis showed a significant difference between the class that used the problem-based learning model with environmental literacy-oriented and the class that used the conventional learning model, with a significant value (2-tailed) of 0.006 < 0.05. In this study, the average post-test score for the experimental class after the treatment was 5.52 higher than the control class Â (78.2 > 72.68). It can be concluded that the environmental literacy-oriented problem-based learning model has a significant effect on the narrative writing skills of elementary school students.Keywords: problem-based learning, environmental literacy, writing skill.AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh problem-based learning berorientasi literasi lingkungan terhadap keterampilan menulis narasi siswa sekolah dasar. Dengan menggunakan metode kuasi eksperimen, penelitian ini menggunakan non-equivalent control group design. Partisipan penelitian ini adalah 50 siswa kelas V MI Darul Qirom, terdiri dari 25 siswa kelas eksperimen dan 25 siswa kelas kontrol. Data diambil melalui instrumen tes yang terdiri dari lima soal uraian tentang menulis narasi. Data yang diperoleh kemudian dianalisis menggunakan uji t dengan bantuan aplikasi SPSS. Analisis data menunjukan adanya perbedaan yang signifikan antara kelas yang menggunakan model pembelajaran problem-based learning berorientasi literasi lingkungan dengan kelas yang menggunakan model pembelajaran konvensional, dengan nilai signifikansi (2 tailed) sebesar 0,006 < 0,05. Pada penelitian ini, nilai rata-rata post-test kelas eksperimen setelah diberikan perlakuan menjadi 5,52 lebih tinggi dibanding kelas kontrol (78,2 > 72,68). Dapat simpulkan bahwa model problem-based learning berorientasi literasi lingkungan berpengaruh signifikan terhadap keterampilan menulis narasi siswa sekolah dasar.Kata kunci: problem-based learning, literasi lingkungan, keterampilan menulis.